1984
DOI: 10.1139/f84-126
|View full text |Cite
|
Sign up to set email alerts
|

Homing and Straying in Chinook Salmon (Oncorhynchus tshawytscha) from Cowlitz River Hatchery, Washington

Abstract: The patterns of homing and straying of spring chinook salmon (Oncorhynchus tshawytscha) from the Cowlitz River, Washington, were analyzed, based on coded wire tag recoveries. Out of an estimated escapement of 41 085 chinook salmon, 98.6% returned to Cowlitz River and the rest were recovered in other rivers. Almost all strays were within the Columbia River system, and most were found in the Lewis and Kalama rivers, upstream of Cowlitz River. Straying was positively correlated with age at return and negatively c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
70
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(79 citation statements)
references
References 8 publications
8
70
1
Order By: Relevance
“…Thus, the collective dynamics create a group-level responsiveness to the environment that is absent at the individual level (19). The resulting increase in gradient-tracking ability for larger groups agrees with previous hypotheses (20,21) and could explain empirical studies showing that grouping facilitates the detection of chemical cues (22)(23)(24) and improves the accuracy of migrations that rely on such cues (25,26).…”
supporting
confidence: 84%
“…Thus, the collective dynamics create a group-level responsiveness to the environment that is absent at the individual level (19). The resulting increase in gradient-tracking ability for larger groups agrees with previous hypotheses (20,21) and could explain empirical studies showing that grouping facilitates the detection of chemical cues (22)(23)(24) and improves the accuracy of migrations that rely on such cues (25,26).…”
supporting
confidence: 84%
“…Furthermore, salmon may benefit from col lective navigation on their homeward journey, i.e. individuals in larger groups can better sense and respond to environmental cues and thereby increase their ability to navigate (Quinn & Fresh 1984, Jonsson & Jonsson 2011, Berdahl et al 2016. Bond et al (2017) compiled data from multiple studies of Chinook salmon Oncorhynchus tshawytscha, and for this species they found strong evidence that rates of successful homing increase with population abundance, consistent with the collective navigation hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…In salmon, some studies suggested that younger fish were less prone to stray than older fish (Quinn et al, 1991;Labelle, 1992), and one study indicated a male sex bias in strays (Hard and Heard, 1999). Both natal and recipient habitat quality may affect straying rate (Quinn and Fresh, 1984;Quinn et al, 1991), but there is no evidence thus far that habitat quality could pre-select fish for straying. The decision whether to stray or to home can be seen as a reflection of the balance of interacting benefits and costs , and the close proximity of creeks and beaches in Little Togiak Lake may allow fish to better assess that balance.…”
Section: Discussionmentioning
confidence: 99%